Financial Reforms and Indian Economy: An Analysis: Exploring the relationship between financial reforms and economic development in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
A financial system is a system of financial foundations, financial markets, financial instruments and financial services to encourage the exchange of assets. The system comprises of savers, middle people, instruments and a definitive client of assets. The dimension of economic development to a great extent relies on and is encouraged by the condition of financial system winning in the economy. Productive financial system and feasible economic development are result and require the conditions for economic development. The financial system prepares the investment funds and channelizes them into the profitable activity and in this way impacts the pace of economic development. Economic development is hampered for need of successful financial system. Extensively, financial system manages three between related and reliant factors, i.e., money, credit and finance.